EVALUASI PENERAPAN SISTEM AKUNTANSI PENGELUARAN KAS ATAS UANG PERSEDIAAN (UP) PADA DINAS SOSIAL KOTA MANADO - Wongkar, Velasco; Pangemanan, Sifrid S.; Wokas, Heince R. N. (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
Efforts by local governments to regulate and manage finances in their own regions in optimizing the capacity of income in each region to improve regional development. This study aims to understand the application of cash accounting system for the Money Supply (UP) at Manado City Social Office. The method used is descriptive quantitative. The results of this study explain the implementation of cash accounting system of cash on inventory (UP) in Manado City Manado has been done in accordance with the theory of accounting system cash disbursement. It is expected that the training in the field of accounting for performance can run well.Keywords: Accounting system cash expenditure, inventory money, implementation effectivenes